Strategi Penggunaan Aplikasi Wordwall Sebagai Sarana Berpikir Mendalam Pada Materi Unsur Bangun Datar di Madrasah Ibtidaiyah - Nor Lailatul Khoiriyah; Shofria Ihda Mahayyun (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Geometry learning in Madrasah Ibtidaiyah often faces challenges because the abstract nature of the elements of plane figures makes it difficult for students to develop a deeper conceptual understanding. This study aims to describe the strategy of using the Wordwall application as a medium for fostering deep thinking in understanding the elements of plane figures among Grade III students at MI Mambaul Ulum Grogolan 02, as well as to identify the supporting and inhibiting factors in its implementation. Data were collected through interviews, observations, and documentation, with validation using source triangulation and technique triangulation. Data analysis used the Miles and Huberman interactive model including data reduction, data display, and conclusion drawing. The results showed that the Wordwall application was integrated with reason-tracking questions (tracking reasons) to trigger Higher Order Thinking Skills (HOTS) and students' self-reflection. Supporting factors include internal factors in the form of students' high motivation and enthusiasm, as well as external factors in the form of school policy support, the availability of digital facilities, and teachers' pedagogical competence. Meanwhile, inhibiting factors include limited time allocation and the availability of technological devices, causing the Wordwall application to be implemented through whole-class group activities, thereby limiting students' opportunities to interact with the media independently. The findings indicate that the successful use of Wordwall as a medium for fostering deep thinking is determined not only by the digital media itself but also by teachers' pedagogical strategies and support from the school environment. This study is expected to serve as a reference for the development of mathematics learning based on deep thinking in elementary education.